Genetic Diversity of Human Enterovirus in Kazakhstan, during 2022 - Dinara Kamalova; Assel Akhmetova; Asylulan Amirgazin; Igor Sytnik; Viktoriya Rudenko; Gulzhan Yessimkhanova; Dinagul Bayesheva; Sergey Yegorov; Alexander Shevtsov (International Journal of Microbiology)
Enteroviral infection is a common cause of aseptic meningitis, herpangina, and hand, foot, and mouth disease in children. Limited data are available on the enteroviral subtypes associated with hospitalization for these conditions in Kazakhstan. We collected cerebrospinal fluid (CSF) and nasopharyngeal swabs (NSW) from children (N = 152, median age = 8 years) hospitalized with symptoms of aseptic meningitis (AM, N = 139) or herpangina (HA, N = 13) disease. We then genotyped enteroviral subtypes associated with AM (n = 50) and HA (n = 9) using next-generation sequencing (NGS) on the viral protein 1 (VP1), followed up by whole-genome sequencing of the isolated viral species. All identified EVs were species B EV, consisting of five echoviruses (E6, E9, E11, E21, and E25) and three coxsackieviruses (CVA9, CVB3, and CVB5) serotypes within the cohort. The most abundant EVs were CVA9 (38.5%), CVB5 (21.5%), and E6 (13.8%). Most HA samples (6/9) were genotyped with coxsackievirus CVA9, while AM was associated with a variety of both echovirus and coxsackievirus serotypes. The results suggest that coxsackievirus CVA9 may be the dominant serotype circulating in the HA population, while AM is more diverse in terms of circulating echovirus and coxsackievirus serotypes. Further studies are needed to determine the clinical implications of these findings and to investigate potential differences in disease severity or outcomes associated with different EV serotypes.